UNMASKING SYNDROMIC HYPOPARATHYROIDISM IN PREGNANCY: A CASE OF BARAKAT SYNDROME - Zulkifle, Aina Mardiah; Karim, Nor Afidah; Adam, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hypoparathyroidism (HypoPT) is a rare endocrine disorder that presents unique challenges in pregnancy due to altered calcium homeostasis. While 75% of cases follow neck surgery, 25% arise from autoimmune, genetic or other causes. During pregnancy, elevated Parathyroid hormone-related peptide (PTHrP) suppresses PTH, while increased 1,25-(OH)₂-D₃ enhances calcium absorption, reducing maternal calcium requirements. Maintaining stable calcium levels is essential to prevent fetal hypocalcemia and secondary hyperparathyroidism. CASE A 24-year-old female at 37 weeks of gestation was incidentally found to have asymptomatic hypocalcemia. Two years earlier, during her first pregnancy, she experienced severe postpartum hypocalcemia accompanied by bilateral lower limb weakness. Investigations revealed a corrected calcium level of 1.65 mmol/L (reference range: 2.18–2.60), phosphate of 1.73 mmol/L (0.78–1.65), iPTH of 0.84 pmol/L (1.56–6.03), and a total 25-hydroxy vitamin D level of 28.88 nmol/L (≥75 nmol/L), leading to a diagnosis of vitamin D deficiency and HypoPT. Unfortunately, she was lost to follow-up. During her current pregnancy, blood tests showed a corrected calcium of 2.04 mmol/L, phosphate of 1.32 mmol/L and iPTH of 2.86 pmol/L. She remained clinically asymptomatic with no signs of hypocalcemia. The goal of management was to maintain calcium levels within the lower normal range until delivery. Further history revealed no prior neck surgery, but she had long-standing bilateral sensorineural hearing loss since childhood. Notably, her parents and siblings also had congenital deafness. Although rare, syndromic causes of HypoPT, such as Barakat syndrome (HDR syndrome), should be considered in patients with hearing impairment, renal disease, or congenital anomalies, especially with a strong family history. CONCLUSION This case highlights the importance of recognising syndromic HypoPT in pregnancy. Barakat syndrome, caused by GATA3 mutations, is characterised by HypoPT, deafness and renal disease, with the full triad in 62.3% of cases and HypoPT with deafness in 28.6%.